Thermotolerant bacteria producing fibrinolytic enzyme - Amid, Azura; Ab. Shukor, Nurul Aqilah (Springer Nature, 2018)
Fibrinolytic enzyme is very useful protease in degrading fibrin for the treatment of thrombosis. Producing the fibrinolytic enzyme at industrial scale involves many steps that require the identified enzyme to be resistant to high temperature, especially during the drying process. Therefore, a thermotolerant enzyme is an advantage, and it is possible to identify this kind of enzyme by isolating the thermotolerant microbe from the hot spring. Thus, this chapter discusses the procedure to isolate fibrinolytic producing-bacteria from a hot spring.